2021
DOI: 10.1126/sciadv.abk3087
|View full text |Cite
|
Sign up to set email alerts
|

Generalizing hydrogel microparticles into a new class of bioinks for extrusion bioprinting

Abstract: Hydrogel microparticles (HMPs) are an emerging bioink that can allow three-dimensional (3D) printing of most soft biomaterials by improving physical support and maintaining biological functions. However, the mechanisms of HMP jamming within printing nozzles and yielding to flow remain underexplored. Here, we present an in-depth investigation via both experimental and computational methods on the HMP dissipation process during printing as a result of (i) external resistance from the printing apparatus and (ii) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 34 publications
4
92
0
Order By: Relevance
“…For JM bioink, the excess water in the interstitial spaces was extruded first, and microgels were packed closer before yielding to flow as previously reported. [23,24] We observed a clogging problem and the discontinuous extrusion of JM bioink during printing (Figure S9c, Supporting Information), which was consistent with previous report; [31] whereas, for MB bioink, microgels (red fluorescent) were evenly extruded with interstitial hydrogel precursor (green fluorescent) due to less resistance (Figure 3a(ii) and Movie S1, Supporting Information). Further, we optimized the 3D printing parameters including the printing speed at 1 mm s −1 and extrusion rate at 0.35 µL s −1 before printing complex structures (Figure S10, Supporting Information).…”
Section: Printability Of Mb Bioinksupporting
confidence: 89%
“…For JM bioink, the excess water in the interstitial spaces was extruded first, and microgels were packed closer before yielding to flow as previously reported. [23,24] We observed a clogging problem and the discontinuous extrusion of JM bioink during printing (Figure S9c, Supporting Information), which was consistent with previous report; [31] whereas, for MB bioink, microgels (red fluorescent) were evenly extruded with interstitial hydrogel precursor (green fluorescent) due to less resistance (Figure 3a(ii) and Movie S1, Supporting Information). Further, we optimized the 3D printing parameters including the printing speed at 1 mm s −1 and extrusion rate at 0.35 µL s −1 before printing complex structures (Figure S10, Supporting Information).…”
Section: Printability Of Mb Bioinksupporting
confidence: 89%
“…Overjamming: Due to more resistance, HMPs were not extruded until rupture of the beads. Reproduced with permission [ 302 ]. Copyright 2021, the Authors.…”
Section: Microcarriers Design Application In Cartilage Tementioning
confidence: 99%
“…5 G). The research results of Xin et al revealed a large enough opening was required for smooth printing of MCs bioinks, but the shape and size of the syringe and nozzle as well as the size and polydispersity of the HMPs must also be considered [ 302 ]. Furthermore, the jamming process within the syringes also affected the printing stability and cytocompatibility.…”
Section: Microcarriers Design Application In Cartilage Tementioning
confidence: 99%
“…We note that the wall resistance can be controlled through the selection of appropriate nozzle opening size compared to the microparticles and that the mechanical properties of hydrogel microparticles also affect the overall printability. For example, Xin et al 123 recently investigated the effect of elastic modulus of PEG‐norbornene hydrogel microparticles by using different MW PEG molecules (PEG5, PEG10, and PEG20). For the same nozzle opening and particle size, microparticles with the highest modulus (PEG5) experience more stress and exhibit higher flow resistance compared to other microparticles, resulting in higher packing.…”
Section: Application Of Mechanically Tailored Soft Microparticlesmentioning
confidence: 99%